Liberal Islamic Thoughts in Indonesia - Radea Y. A. Hambali; Leonardus Samosir (FOCUS, 2022)
The understanding of freedom of thought in Islam which is the soul / spirit of the liberal Islamic movement that grows in the context of Islamic thinking in Indonesia originates from Islamic tradition; although in its development Western modernization has also colored liberal Islamic discourse. Therefore, liberal ideas need not always be understood in the Western context and by using Western barometers. On the other hand, liberal Islam can be understood in the sense of those who are opposed to revivalism that often discusses orthodox themes that are considered established, such as Islamic teachings on politics, democracy, women's rights, religious pluralism, freedom of thought and ideas about progress. By always re-enacting these themes, liberal Islamic groups believe that Islam will be able to play an important role in the contemporary world. Furthermore, the development of liberal Islam in Indonesia cannot be separated from the context of the development of the understanding of the liberalization of Islamic thought in the Islamic world. Included in this case is the treatment that often discredits liberal Islamic groups that occur both in the Muslim world and in Indonesia.